Estimation of temperature and electron density in stainless steel plasma using laser induced breakdown spectroscopy - Halid, N. S. T. (Penerbit UTM Press, 2016)
LIBS plasma produced by a 1064 nm Q-switched Nd:YAG laser in an atmospheric pressure was studied for the stainless steel sample. The laser output energy 150 mJ with pulse duration of 6 ns. The plasma emission spectrum was recorded by the LR1 Spectrometer connected to the fibre optic. The plasma temperature and electron density of each element were estimated by time-resolved spectroscopy of neutral atom and ion line emission. The plasma temperature was obtained from the Boltzmann plot method and their electron density was determined by using Saha-Boltzmann equation method. The preliminary qualitative LIBS analysis shows that several elements contained in the stainless steel. The element detected was Cu, Fe, Mn, Ni, and Cr. The results shows that Mn and Fe has the highest plasma temperature of 1.2 eV, but the electron density of Mn was the highest with value 4.6x1020 cm-3, while the Cu has the lowest temperature that is 0.73 eV with the electron density 2.8x1017 cm-3. The results are discussed.